Crew and aircraft recovery through a multi-agent airline electronic market - Andreia Malucelli (2006)
Airline companies do not collaborate when dealing with problems that arise during their own operational control plan. These problems are related with aircrafts, crew members and passengers and the actions towards the solution of these problems are usually known as operations recovery. In this paper we present a possible solution to the problem of lack of collaboration between different airlines, based on an electronic market. This electronic market is based on a Distributed Multi-Agent System we are developing to help airline companies in solving unexpected operations recovery problems and matching them with potential solutions. The proposed electronic market uses ontology services that we have developed for other domains, allowing an airline company to access resources of other airline companies, such as aircrafts and crew members. The potential solutions obtained through the electronic market interactions will compete with the solutions found by the airline company own system. We present a real case study taken from TAP Air Portugal operational control including the description of how the ontologies services work. We believe that using our system architecture and services for this application domain is a possible and interesting solution but we are also aware of challenges and problems that might arise from using this approach.